2018
DOI: 10.31548/dopovidi2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Influence Of Endophytic And Saprotrophic Penicillium Funiculosum Strains On Resistance Of Glycine Max L. Under Salt Stress

Abstract: Endophytic fungi characterized by wide biodiversity and formed an important component of plant ecosystems. Endophytic fungi play a significant role in the growth and development of plants under biotic and abiotic stresses. Influence of endophytic and saprotrophic Penicillium funiculosum strains on resistance of Glycine max L. under salt stress was studied. It was shown that under salinity stress (70 mM and 140 mM NaCl, respectively) endophyte P. funiculosum significantly promoted soybean growth attributes (sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Hamayun et al (2010) revealed that endophytic could reduce the negative eff ects of salinity and progress plant germination, emergence, growth, and biomass production, by synthesizing phytohormones (gibberellins: GA1, GA4, GA8 and GA9, indole-acetic acid: IAA and abscissic acid: ABA). Also, Yurieva et al (2018) reported that Penicillium funiculosum stimulated soybean growth and improved the dry root biomass. Furthermore, Ahmad et al (2015) showed that the increase in plant growth and biomass production after Trichoderma spp.…”
Section: Resultsmentioning
confidence: 99%
“…Hamayun et al (2010) revealed that endophytic could reduce the negative eff ects of salinity and progress plant germination, emergence, growth, and biomass production, by synthesizing phytohormones (gibberellins: GA1, GA4, GA8 and GA9, indole-acetic acid: IAA and abscissic acid: ABA). Also, Yurieva et al (2018) reported that Penicillium funiculosum stimulated soybean growth and improved the dry root biomass. Furthermore, Ahmad et al (2015) showed that the increase in plant growth and biomass production after Trichoderma spp.…”
Section: Resultsmentioning
confidence: 99%